Indole-3 Carbinol and Diindolylmethane Mitigated β-Amyloid-Induced Neurotoxicity and Acetylcholinesterase Enzyme Activity: In Silico, In Vitro, and Network Pharmacology Study - Ramakrishna K.; Karuturi P.; Siakabinga Q.; T.A G.; Krishnamurthy S.; Singh S.; Kumari S.; Kumar G.S.; Sobhia M.E.; Rai S.N. (My University, 2025)
Background: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by beta-amyloid (Aβ) deposition and increased acetylcholinesterase (AchE) enzyme activities. Indole 3 carbinol (I3C) and diindolylmethane (DIM) are reported to have neuroprotective activities against various neurological diseases, including ischemic stroke, Parkinson’s disease, neonatal asphyxia, depression, stress, neuroinflammation, and excitotoxicity, except for AD. In the present study, we have investigated the anti-AD effects of I3C and DIM. Methods: Docking and molecular dynamic studies against AchE enzyme and network pharmacological studies were conducted for I3C and DIM. I3C and DIM’s neuroprotective effects against self and AchE-induced Aβ aggregation were investigated. The neuroprotective effects of I3C and DIM against Aβ-induced neurotoxicity were assessed in SH-S5Y5 cells by observing cell viability and ROS. Results: Docking studies against AchE enzyme with I3C and DIM show binding efficiency of −7.0 and −10.3, respectively, and molecular dynamics studies revealed a better interaction and stability between I3C and AchE and DIM and AchE. Network pharmacological studies indicated that I3C and DIM interacted with several proteins involved in the pathophysiology of AD. Further, I3C and DIM significantly inhibited the AchE (IC50: I3C (18.98 µM) and DIM (11.84 µM)) and self-induced Aβ aggregation. Both compounds enhanced the viability of SH-S5Y5 cells that are exposed to Aβ and reduced ROS. Further, I3C and DIM show equipotential neuroprotection when compared to donepezil. Conclusions: Our findings indicate that both I3C and DIM show anti-AD effects by inhibiting the Aβ induced neurotoxicity and AchE activities. © 2024 by the authors.